KARAKTERISTIK GENERATOR SINKRON MODIFIKASI DENGAN EKSITASI TERPISAH - , MUHAMMAD ISMAIL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development of technology makes demand for electricity increases, and the government has to diversify their energy production. One of the energy resources is picohydro power plant, because Indonesia has many rivers. This power plant is able to supply household electricity, less than 500 watt. But the problem is that plant needs low speed generator, that is rarely in Indonesia. Thus practitioner has to modify their generators to be used in low speed less than 1000 rpm. This study use sychronous generator as model by modifying rotor and stator windings. To determine its performance, characterization on 600 rpm speed with separate excitation direct current resources is performed. The characteristics are no-load, load, no-control and control. In no-load characteristic, constant speed (n) is 665 rpm. Increasing excitation current (If) makes electromotive force (Ea) increases, till a rotor saturated. Ea maximal = 195 volt and If = 130 mA. In load characteristic, constant speed (n) is 665 rpm and constant load current (IL) is 160 mA. A load current (IL) can cause terminal voltage drop. Vt maximal = 95 volt, If = 120 mA. In no-control characteristic, constant excitation current (If) is 100 mA. Increasing load current (IL) can cause terminal voltage (Vt) and speed (n) are decrease. In control characteristic, constant terminal voltage (Vt) is 90 volt. Increasing load current (IL) makes excitation current (If) excess so that a synchronous generator stable.